Chemical Composition of Ailanthus altissima (Mill.) Swingle Methanolic Leaf Extracts and Assessment of Their Antibacterial Activity through Oxidative Stress Induction - Halima Boukhibar; Aicha Laouani; Soraya Naila Touzout; Rawaf Alenazy; Mohammed Alqasmi; Yaseen Bokhari; khaled Saguem; Mossadok Ben-Attia; Safia El-Bok; Abderrahmen Merghni (MDPI AG, 2023)
The present study was conducted to investigate the chemical composition of Ailanthus altissima (Mill.) Swingle methanolic leaf extracts from geographically distinct regions and to assess their antimicrobial properties along with their ability to induce oxidative stress. The HPLC-DAD analysis revealed the presence of phenolic acids and flavonoids including chlorogenic acid, gallic acid, synapic acid, p-coumaric acid, apigenin, hyperoside, isoamnétine-3-O-beta-D-glucotrioside, quercetin, and isoquercetin in various amounts depending on the origin of tested extracts. The assessment of antibacterial activity showed the effectiveness of the A. altissima extracts particularly against Gram-positive bacteria, with inhibition zone diameters reaching 14 ± 1 mm and minimum inhibitory concentrations ranging from 4 to 72.2 mg/mL. These bioactive substances also exhibited strong antibiofilm activity with an eradication percentage reaching 67.07%. Furthermore, they increased ROS production to levels two to five times higher than the control group, altered the membrane integrity and caused lipid peroxidation with MDA production exceeding 2.5 µmol/mg protein in the Gram-positive and Gram-negative strains. A decrease in the levels of the antioxidant enzymes SOD and CAT was also observed, indicating an impairment of the bacterial response to the oxidative stress caused by the tested extracts. These findings highlight the antibacterial properties of A. altissima leaf extracts depending on their origins and promote their exploitation and application in the agro-food and pharmaceutical sectors.